(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To assess serum levels of tumor necrosis factor-alpha (TNF-?) in uveitis patients with optic nerve inflammation (ONI). Materials and Methods: A retrospective evaluation of 132 patients who underwent examination and treatment for uveitis with ONI was performed. A commercially available enzyme-linked immunosorbent assay kit was used to measure serum TNF-? levels. Serum samples of 30 healthy donors were used as controls. Results: Serum TNF-? levels in uveitis patients with ONI were 3.8 times higher compared to those in healthy controls (15.8 ± 1.02 pg/mL and 4.1 ± 1.52 pg/mL, respectively, p < 0.05). The highest increase in serum TNF-? levels compared to controls was seen in intermediate uveitis. Conclusion: Serum TNF-? levels in active period of uveitis with ONI were found to be statistically significantly increased compared to those in controls. This finding provides the rationale for the use of anti-TNF-? agents for the treatment of uveitis with optic nerve inflammation.